Development of Question-Based Exercise Books Minimum Competency Assessment for Students SMP - Erika Anugra Heni; Tri Novita Irawati; Sholahudin Al Ayubi (Formosa Journal of Social Sciences (FJSS), 2023)
The background of this research is the need for AKM-based question practice books in implementing AKM in schools for junior high school students. This study aims to describe the process and results of developing a test book based on the Minimum Competency Assessment (AKM) for junior high school students. The type of research used is Research and Development (R&D) with the ADDIE model which consists of five stages, namely, 1) Analysis, 2) Design, 3) Development, 4) Implementation, 5) Evaluation. The results of the AKM-based question practice book for junior high school students based on 2 material expert validators according to table 3.5 the classification of conversion of quantitative data to qualitative data, by validator 1 from the aspect of content eligibility and language eligibility aspects got a score of 3.86 and 3.69 in the "good" category . While the results of material validation by validator 2 from the aspect of content feasibility and language feasibility aspects scored 4.13 and 4.23 in the "good" and "very good" categories. The results of media expert validation from the graphical feasibility aspect and the presentation feasibility aspect, by validator 1 getting a score of 3.96 and 3.88 are in the "good" category, while validator 2 is getting a score of 4.65 and 4.55 in the "very good" category